Novel solid-phase strategy for the synthesis of ligand-targeted fluorescent-labelled chelating peptide conjugates as a theranostic tool for cancer - Sengupta, Sagnik; Krishnan, Mena Asha; Dudhe, Premansh; Reddy, Ramesh B.; Giri, Bishnubasu; Chattopadhyay, Sudeshna; Chelvam, Venkatesh (Beilstein Journal of Organic Chemistry, 2018)
In this article, we have successfully designed and demonstrated a novel continuous process for assembling targeting ligands, peptidic spacers, fluorescent tags and a chelating core for the attachment of cytotoxic molecules, radiotracers, nanomaterials in a standard Fmoc solid-phase peptide synthesis in high yield and purity. The differentially protected Fmoc-Lys-(Tfa)-OH plays a vital role in attaching fluorescent tags while growing the peptide chain in an uninterrupted manner. The methodology is versatile for solid-phase resins that are sensitive to mild and strong acidic conditions when acid-sensitive side chain amino protecting groups such as Trt (chlorotrityl), Mtt (4-methyltrityl), Mmt (4-methoxytrityl) are employed to synthesise the ligand targeted fluorescent tagged bioconjugates. Using this methodology, DUPA rhodamine B conjugate (DUPA = 2-[3-(1,3-dicarboxypropyl)ureido]pentanedioic acid), targeting prostate specific membrane antigen (PSMA) expressed on prostate, breast, bladder and brain cancers and pteroate rhodamine B, targeting folate receptor positive cancers such as ovarian, lung, endometrium as well as inflammatory diseases have been synthesized. In vitro studies using LNCaP (PSMA +ve), PC-3 (PSMA −ve, FR −ve) and CHO-β (FR +ve) cell lines and their respective competition experiments demonstrate the specificity of the newly synthesized bioconstructs for future application in fluorescent guided intra-operative imaging.
Keywords: chelating linker; confocal studies; continuous synthetic process; fluorescent tag; Fmoc-Lys-(Tfa)-OH; prostate cancer and ovarian cancer; solid-phase peptide synthesis

(untitled) - Srinivasarao, M.; Low, P. S. (Chem. Rev., 2017)

(untitled) - Bernsen, M. R.; Kooiman, K.; Segbers, M.; van Leeuwen, F. W. B.; de Jong, M. (Eur. J. Nucl. Med. Mol. Imaging, 2015)

(untitled) - Yankeelov, T. E.; Abramson, R. G.; Quarles, C. C. (Nat. Rev. Clin. Oncol., 2014)

(untitled) - Gao, M.; Yu, F.; Lv, C.; Choo, J.; Chen, L. (Chem. Soc. Rev., 2017)

(untitled) - Cutler, C. S.; Hennkens, H. M.; Sisay, N.; Hucklier-Markai, S.; Jurisson, S. S. (Chem. Rev., 2013)

(untitled) - Mather, S. (Bioconjugate Chem., 2009)

(untitled) - Chang, S. S. (Rev. Urol., 2004)

(untitled) - Barrio, M.; Fendler, W. P.; Czernin, J.; Herrmann, K. (Expert Rev. Mol. Diagn., 2016)

(untitled) - Ristau, B. T.; O’Keefe, D. S.; Bacich, D. J. (Urol. Oncol.: Semin. Orig. Invest., 2014)

(untitled) - Kalli, K. R.; Oberg, A. L.; Keeney, G. L.; Christianson, T. J. H.; Low, P. S.; Knutson, K. L.; Hartmann, L. C. (Gynecol. Oncol., 2008)

(untitled) - Lutz, R. J. (Transl. Cancer Res., 2015)

(untitled) - Sega, E. I.; Low, P. S. (Cancer Metastasis Rev., 2008)

(untitled) - Low, P. S.; Kularatne, S. A. (Curr. Opin. Chem. Biol., 2009)

(untitled) - Lu, Y.; Stinnette, T. W.; Westrick, E.; Klein, P. J.; Gehrke, M. A.; Cross, V. A.; Vlahov, I. R.; Low, P. S.; Leamon, C. P. (Arthritis Res. Ther., 2011)

(untitled) - Jager, N. A.; Teteloshvili, N.; Zeebregts, C. J.; Westra, J.; Bijl, M. (Autoimmun. Rev., 2012)

(untitled) - Low, P. S.; Henne, W. A.; Doorneweerd, D. D. (Acc. Chem. Res., 2008)

(untitled) - van Dam, G. M.; Themelis, G.; Crane, L. M. A.; Harlaar, N. J.; Pleijhuis, R. G.; Kelder, W.; Sarantopoulos, A.; de Jong, J. S.; Arts, H. J. G.; van der Zee, A. G. J.; Bart, J.; Low, P. S.; et al. (Nat. Med., 2011)

(untitled) - Keating, J. J.; Okusanya, O. T.; De Jesus, E.; Judy, R.; Jiang, J.; Deshpande, C.; Nie, S.; Low, P.; Singhal, S. (Mol. Imaging Biol., 2016)

(untitled) - Kennedy, G. T.; Okusanya, O. T.; Keating, J. J.; Heitjan, D. F.; Deshpande, C.; Litzky, L. A.; Albelda, S. M.; Drebin, J. A.; Nie, S.; Low, P. S.; Singhal, S. (Ann. Surg., 2015)

(untitled) - Okusanya, O. T.; DeJesus, E. M.; Jiang, J. X.; Judy, R. P.; Venegas, O. G.; Deshpande, C. G.; Heitjan, D. F.; Nie, S.; Low, P. S.; Singhal, S. J. (Thorac. Cardiovasc. Surg., 2015)

(untitled) - Tummers, Q. R. J. G.; Hoogstins, C. E. S.; Gaarenstroom, K. N.; de Kroon, C. D.; van Poelgeest, M. I. E.; Vuyk, J.; Bosse, T.; Smit, V. T. H. B. M.; van de Velde, C. J. H.; Cohen, A. F.; Low, P. S.; Burggraaf, J.; et al. (Oncotarget, 2016)

(untitled) - Kelemen, L. E. (Int. J. Cancer, 2006)

(untitled) - Bouchelouche, K.; Choyke, P. L.; Capala, J. (Discov. Med., 2010)

(untitled) - Jin, W.; Qin, B.; Chen, Z.; Liu, H.; Barve, A.; Cheng, K. (Int. J. Pharm., 2016)

(untitled) - Zhao, X.; Li, H.; Lee, R. J. (Expert Opin. Drug Delivery, 2008)

(untitled) - Rink, H. (Tetrahedron Lett., 1987)

(untitled) - Bollhagen, R.; Schmiedberger, M.; Barlos, K.; Grell, E. (J. Chem. Soc., Chem. Commun., 1994)

(untitled) - Mergler, M.; Nyfeler, R.; Tanner, R.; Gosteli, J.; Grogg, P. (Tetrahedron Lett., 1988)

(untitled) - Sieber, P. (Tetrahedron Lett., 1987)

(untitled) - Aletras, A.; Barlos, K.; Gatos, D.; Koutsogianni, S.; Mamos, P. (Int. J. Pept. Protein Res., 1995)

(untitled) - Zhao, N.; Williams, T. M.; Zhou, Z.; Fronczek, F. R.; Sibrian-Vazquez, M.; Jois, S. D.; Vicente, M. G. H. (Bioconjugate Chem., 2017)

(untitled) - Kuil, J.; Buckle, T.; Yuan, H.; van den Berg, N. S.; Oishi, S.; Fujii, N.; Josephson, L.; van Leeuwen, F. W. B. (Bioconjugate Chem., 2011)

(untitled) - Napp, J.; Stammes, M. A.; Claussen, J.; Prevoo, H. A. J. M.; Sier, C. F. M.; Hoeben, F. J. M.; Robillard, M. S.; Vahrmeijer, A. L.; Devling, T.; Chan, A. B.; de Geus-Oei, L.-F.; Frauke, A. (Int. J. Cancer, 2018)

(untitled) - Viehweger, K.; Barbaro, L.; García, K. P.; Joshi, T.; Geipel, G.; Steinbach, J.; Stephan, H.; Spiccia, L.; Graham, B. (Bioconjugate Chem., 2014)

(untitled) - Xing, T.; Yang, X.; Wang, F.; Lai, B.; Yan, L. (J. Mater. Chem., 2012)

(untitled) - Kularatne, S. A.; Wang, K.; Santhapuram, H.-K. R.; Low, P. S. (Mol. Pharmaceutics, 2009)

(untitled) - Kelderhouse, L. E.; Chelvam, V.; Wayua, C.; Mahalingam, S.; Poh, S.; Kularatne, S. A.; Low, P. S. (Bioconjugate Chem., 2013)

(untitled) - Kularatne, S. A.; Zhou, Z.; Yang, J.; Post, C. B.; Low, P. S. (Mol. Pharmaceutics, 2009)

(untitled) - Kozikowski, A. P.; Zhang, J.; Nan, F.; Petukhov, P. A.; Grajkowska, E.; Wroblewski, J. T.; Yamamoto, T.; Bzdega, T.; Wroblewska, B.; Neale, J. H. (J. Med. Chem., 2004)

(untitled) - Ross, T. L.; Honer, M.; Müller, C.; Groehn, V.; Schibli, R.; Ametamey, S. M. (J. Nucl. Med., 2010)

(untitled) - Leamon, C. P.; You, F.; Santhapuram, H. K.; Fan, M.; Vlahov, I. R. (Pharm. Res., 2009)

(untitled) - Mesters, J. R.; Barinka, C.; Li, W.; Tsukamoto, T.; Majer, P.; Slusher, B. S.; Konvalinka, J.; Hilgenfeld, R. (EMBO J., 2006)

(untitled) - Li, D.; Elbert, D. L. (J. Pept. Res., 2002)

(untitled) - Moroder, L.; Filippi, B.; Borin, G.; Marchiori, F. (Biopolymers, 1975)

(untitled) - Pazos, E.; Vázquez, O.; Mascareñas, J. L.; Vázquez, M. E. (Chem. Soc. Rev., 2009)

(untitled) - Benešová, M.; Schäfer, M.; Bauder-Wüst, U.; Afshar-Oromieh, A.; Kratochwil, C.; Mier, W.; Haberkorn, U.; Kopka, K.; Eder, M. (J. Nucl. Med., 2015)

(untitled) - Kularatne, S. A.; Chelvam, V.; Santhapuram, H.-K. R.; Wang, K.; Vaitilingam, B.; Henne, W. A.; Low, P. S. (J. Med. Chem., 2010)